Systemic Literature Review: Students' Perception of Teachers' Social Competence - Nasir, Muhammad; Adawiyah, Rizky Noor; Wulansari, Bella Indriati (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2024)
This research uses a qualitative approach, namely a research design that aims to explore the meaning, perception, experience, and literature studies. Qualitative research is a stage of research that seeks to understand and produce data in the form of certain phenomena, behaviors, and situations based on the researcher's own perspective Specifically, the method used in this article is a literature study, which is the study of books and other references that are relevant to the problem being researched (Sarwono, 2006). This study aims to analyze students' perception of teachers' social competence through the systematic literature review method. The results of literature analysis show that students' perception of teachers' social competence has a significant influence on the assessment of educational effectiveness. These findings underscore the importance of efforts to improve teachers' social competence through training, discussion, and professional development. The implication of this literature review is the need to develop more focused strategies and programs to improve teachers' social competence and increase cooperation between schools, parents, and learning environments in supporting effective and positive learning for students at various levels of education.